Endovascular Thrombectomy Versus Medical Management in Isolated M2 Occlusions: Pooled Patient‐Level Analysis from the EXTEND‐IA Trials, INSPIRE, and SELECT Studies. Issue 5 (17th March 2022) - Sarraj, Amrou; Parsons, Mark; Bivard, Andrew; Hassan, Ameer E.; Abraham, Michael G.; Wu, Teddy; Kleinig, Timothy; Lin, Longting; Chen, Chushuang; Levi, Christopher; Dong, Qiang; Cheng, Xin; et al.
Abstract : Objective: The objective of this study was to evaluate functional and safety outcomes of endovascular thrombectomy (EVT) versus medical management (MM) in patients with M2 occlusion and examine their association with perfusion imaging mismatch and stroke severity. Methods: In a pooled, patient‐level analysis of 3 randomized controlled trials (EXTEND‐IA, EXTEND‐and IA‐TNK parts 1 and 2) and 2 prospective nonrandomized studies (INSPIRE and SELECT), we evaluated EVT association with 90‐day functional independence (modified Rankin Scale [mRS] = 0–2) in isolated M2 occlusions as compared to medical management overall and in subgroups by mismatch profile status and stroke severity. Results: We included 517 patients (EVT = 195 and MM = 322), baseline median (interquartile range [IQR]) National Institutes of Health Stroke Scale (NIHSS) was 13 (8–19) in EVT versus 10 (6–15) in MM, p < 0.001. Pretreatment ischemic core did not differ (EVT = 10 [0–24] ml vs MM = 9 [3–21] ml, p = 0.59). Compared to MM, EVT was more frequently associated with functional independence (68.3 vs 61.6%, adjusted odds ratio [aOR] = 2.42, 95% confidence interval [CI] = 1.25–4.67, p = 0.008, inverse probability of treatment weights [IPTW]‐OR = 1.75, 95% CI = 1.00–3.75, p = 0.05) with a shift toward better mRS outcomes (adjusted cOR = 2.02, 95% CI:1.23–3.29, p = 0.005), and lower mortality (5 vs 10%, aOR = 0.32, 95% CI = 0.12–0.87, p = 0.025). EVT was associated with higher functional independence in patients with a perfusion mismatch profile (EVT = 70.7% vs MM = 61.3%, aOR = 2.29, 95% CI = 1.09–4.79, p = 0.029, IPTW‐OR = 2.02, 1.08–3.78, p = 0.029), whereas no difference was found in those without mismatch (EVT = 43.8% vs MM = 62.7%, p = 0.17, IPTW‐OR: 0.71, 95% CI = 0.18–2.78, p = 0.62). Functional independence was more frequent with EVT in patients with moderate or severe strokes, as defined by baseline NIHSS above any thresholds from 6 to 10, whereas there was no difference between groups with milder strokes below these thresholds. Interpretation: In patients with M2 occlusion, EVT was associated with improved clinical outcomes when compared to MM. This association was primarily observed in patients with a mismatch profile and those with higher stroke severity. ANN NEUROL 2022;91:629–639